COTTONSEED OIL DEODORIZATION PROCESS IN MATHEMATICAL MODELING - PhD. Д. Ж. Хужакулова; Э. Насриддинов; Б. Ҳамроев (Galaxy International Interdisciplinary Research Journal, 2024)
Planning and modeling is a progressive method of studying chemical and technological processes, which makes it possible to optimize existing technological processes and improve the quality of products [1-4]. The use of these methods in experimental studies significantly reduces the number of studies and provides more reliable results. Not enough research has been done in the direction of planning and modeling of cottonseed oil deodorization processes. Therefore, the study of these issues is of scientific and practical interest.